Development of a web-based poedji rochjati score information system for early detection of high-risk pregnancy - Lestari, Humaediah; Irfan, Pahrul; Azamti, Baiq Nova Aprilia (Science Midwifery, 2026)
Maternal mortality remains a critical public health issue that can be reduced through effective early detection of high-risk pregnancies. In Indonesia, the Poedji Rochjati Score Card (KSPR) is widely used as a screening tool; however, its implementation is predominantly manual, leading to inefficiencies in data management, risk classification, and continuity of antenatal care. This study aims to develop a web-based Poedji Rochjati Score to support early detection of high-risk pregnancies at the primary healthcare level. This research employed an applied research and development design using the Rapid Application Development (RAD) method. The results indicate that the developed system successfully automates KSPR scoring and pregnancy risk classification based on standardized criteria. The system improves the accuracy and consistency of risk assessment, enhances maternal health data management, and supports longitudinal monitoring of pregnancy risk status. Implementation findings show that the system facilitates more efficient antenatal care services and provides structured risk reports to support clinical and referral decision-making. This study contributes to applied health informatics by demonstrating how standardized maternal risk screening can be effectively digitalized at the primary healthcare level. In conclusion, the web-based Poedji Rochjati Score information system offers an effective and innovative solution for strengthening early detection of high-risk pregnancies. The integration of a standardized screening tool with digital technology enhances screening accuracy, service efficiency, and data continuity in antenatal care. This study provides a practical foundation for further development and wider implementation of digital maternal health screening systems to support improved maternal healthcare quality.